Improvement of the efficiency of treatment in patients with coronary artery disease and metabolic syndrome after percutaneous coronary intervention for acute coronary syndrome without ST-segment elevation - Chumachenko N.V. (Medičnì Perspektivi, 2016)
The paper presents original data on improvement of effectiveness of treatment (reduction of systemic inflammation, stabilization of lipid metabolism, improvment of quality of life) in patients with coronary artery disease (CAD) and metabolic syndrome (MS), who underwent primary percutaneous coronary intervention (PCI) for acute coronary syndrome without ST-segment elevation (ACS nST) by adding quercetin to basic therapy, 40 mg 3 times a day during the 12,07 ± 1,51 months. The reduction of a high sensitive C-reactive proteins (hs-CRP), (2,51 ± 0,93, nmol / L., versus 3,12 ± 0,43, nmol / L.), (p = 0,0007) and low-density lipoproteins (LDL), (4,01 ± 0,36, mmol / L., versus 4,29 ± 0,71, mmol / L.), (p=0,049) in the main group II (n = 33) as compared with the control group I (n=31), respectively, as well as thrombin: 5,96 ± 1,89, ng / mL. in group I as compared with 3,91 ± 1,43, ng / mL. in group II, (p=0,0002) was revealed. High density lipoproteins (HDL) were significantly greater (p = 0,049) in the group II (1,35 ± 0,41, mmol / L.) in comparison with the group I (1,17 ± 0,34, mmol / L.).